Genotype-environment interactions in Vernonia Galamensis - Genet, Tsige (Ethiopian Journal of Science and Technology, 2024)
Seed yield of nine Vernonia galamensis genotypes, tested in a randomised complete design with three replications across six environments in Ethiopia (three locations and two years) was analysed using different stability models. The objectives were to assess genotype-environment (G-E) interactions, determine stable genotypes, and to compare the stability models. Combined analysis of variance across locations indicated that year, location and genotype by year were the most dominant source of interactions. Highly significant rank correlations were found among stability variance, ecovalence and additive main effects multiplicative interactions that indicated their close similarity and effectiveness in detecting stable genotypes over a range of environments. The stability analyses identified 'Boke Kuni' as more stable genotype and 'Gelemso' specifically adapted to some environments.